Identification and expression of HySmad1, a member of the R-Smad family of TGFβ signal transducers, in the diploblastic metazoan Hydra - Hobmayer, Bert; Rentzsch, Fabian; Holstein, Thomas W. (Development genes and evolution, 2001)
Members of the Smad family of TGFβ signal transducers are important regulators of proliferation and cell fate during axis formation, organogenesis, and tumorigenesis. A canonical TGFβ/Smad signaling p
Gesehen am 26.01.2017